Early Philosophical Shi'ism - Mehdi Aminrazavi (International Institute of Islamic Thought, 1995)
Early Philosophical Shi'ism is a comprehensive study of the Isma'ili thinker and neoplatonist, Abu Ya'qub al Sijistani. Chapter one, which follows a brief preface that presents some general remarks about al Sijistani and the book's structure discusses "The Ismaili Message and It Philosophers." He first explains the origin of the Ismailis and their doctrine of authority and then alludes to the concept of imiimah and its relationship to occultation (ghaybah). After this, Walker deals with the concept of da'wah from it origin to its subsequent historical development. Several Ismaili dais, among them al Razi, al Kirmani, Nasir-i Khusraw, and al Shirazi, are discussed briefly, as are the role of early dais and the concept of hermenuetics (ta'wil). Walker begins with Iran in order to provide a background to da'wah in that land and also analyzes the massacre of al Na afi and his followers. The author, having offered an account of Sijistani's biography and the evolution of some of his thoughts, brings the chapter to an end by introducing his works and placing particular emphasis on al Yanabi', al Maqalid, al lftikhar, and Sullam al Najat ...